Leveraging Canva to create a biographical recount text for vocational secondary students in ESP instruction - Pratiwi, Wahyuni (Englisia: Journal of Language, Education, and Humanities, 2024)
Integrating technology into English for Specific Purposes (ESP) instruction is essential for adapting to rapid technological advancements, and Canva offers significant potential in this area. However, research on Canva has mainly focused on general English instruction, with limited examination of its application in ESP. This study explores how vocational secondary school teachers used Canva to teach biographical recount texts in an ESP context, along with the rationale behind this choice. A qualitative study was conducted at SMKN 13 Malang, West Java, within the Merchant Nautical Ship Department. Data were collected through classroom observation and interviews with an experienced English teacher. Observations revealed the structured steps of using Canva to teach biographical recount texts, enabling more active students’ participation in class. Canva was chosen for its practical benefits, including students’ familiarity with the platform, ready-to-use templates, and the potential to boost students’ creativity, all of which support its effective use in vocational education.